Inovatívne prístupy k monitorovaniu organických kontaminantov vo vodnom prostredí použitím pasívneho vzorkovania - Lobpreis, Tomáš; Vrana, Branislav; Dercová, Katarína (Chemické listy, 2009)
The aim of this review is to introduce new methods of monitoring organic contaminants in aqueous environment. Passive sampling devices are able to overcome many of the limitations associated with conventional spot sampling of waters. They work in the integrative mode allowing the estimation of time-weighted average concentrations of contaminants in water, soil, sediments or air. Unlike most monitoring methods, passive samplers measure the dissolved, i.e. bioavailable fraction of water pollutants. In addition, they are able to effectively concentrate the pollutants that are present in trace amounts. The passive sampling devices should not replace conventional sampling; they provide additional information on the environment pollution at a reasonable cost.
Keywords: Water Pollutants, Chemical; Environmental Monitoring; Water Pollution, Chemical; monitorování životního prostředí; chemické látky znečišťující vodu; chemické znečištění vody